Pseudomixoma peritonei, una revisión bibliográfica actualizada - Chaves Chaves, Alejandra (2019)
Pseudomyxoma peritonei (PMP) is a condition characterized by progressive accumulation of mucinous ascites and implantation of mucinous tumors in the peritoneal cavity. This article is a bibliographic review in which 44 bibliographical sources were used. From the information collected, we can say that the PMP is a rare disease, which has the epithelial neoplasms of the appendix as its main etiology. Its clinic is classically presented with vague abdominal symptoms. The most used diagnostic method is CT. Its treatment is based on surgical resection together with intraperitoneal chemotherapy (HIPEC), a method that has shown, in recent years, to increase survival compared to traditional therapy (only surgical resection). However, the research studies carried out so far have been with small populations, of a retrospective type and are not multicentric, for which reason there is not enough evidence to support the definitive management for this pathology